PEMETAAN TINGKAT BAHAYA EROSI LAHAN KERING DI KECAMATAN JATIPURO KABUPATEN KARANGANYAR DENGAN SISTEM INFORMASI GEOGRAFI (SIG) - Robby Eko Christanto; Suryono Suryono; Mujiyo Mujiyo; Joko Winarno (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2010)
Title : The Degree of Erosion Hazard Mapping in Dry Land at Jatipuro Sub District of Karanganyar with Geographic Information System (GIS). This research had been conducted at Jatipuro, Sub District of Karanganyar from July until September, 2007. The aims of this research are to know degree of erosion danger and to map that degree of erosion danger. This research was descriptive-explorative by field’s survey and laboratory analysis. Soil sampling technique using purposive sampling method. Site sampling determined with land mapping unit. Analysis of erosion level using USLE method, even though to know degree of erosion dangerous used the table of relation soil depth with erosion level. To make the map degree of erosion dangerous with Arc view GIS 3.3 software. The result of this research conclude that Jatipuro, Sub District of Karanganyar can be classified into 4 erosion dangerous class, with position and width area such that very light in 6th land mapping unit with width area 8.53 ha or 1.17% from total wide of research area. Light, in 1st, 4th, 7th, 12tnd and 16th land mapping units with width area 245.36 ha or 33.72% from total wide of research area. Middle class, in 2nd, 8th, 9th, 10th, 14th, 15th, 17th and 18th land mapping units with width area 181.59 ha or 24.95% from total wide area. Heavy class, in 3rd, 5th, 11th, 13th, 19th, 20th, 21st and 22nd land mapping units with width area 292.18 ha or 40.15% from total wide area. The management of conservation in the land with degree of erosion danger very light until light is low tillage applications, which this purpose is to create soil condition that supported growth of root, but also must be understood the result of tillage, which can be broken soil structures. For the lands with degree of erosion danger middle until heavy, the better conservation is needed. These lands needed terrace’s repairing, there are making bench terrace with middle construction for the middle class and more better terrace for the heavy one. For the best result to minimalist erosion level in this location, in terrace’s making also needed vegetative conservation, there is strip grass to strength the terrace, and also mulching. Keywords: degree of erosion hazard, dry land, GIS